REFORESTACIÓN DE TIERRAS AGRARIAS CON ENCINA Y COSCOJA. UN CASO EN TOLEDO - BARREDA, A; SOBRINI, I (III Congreso Forestal Español Congreso, 2001)
The Holm Oak (Quercus ilex) and the Kermes Oak (Quercus coccifera), both together, are being used successfuly in the dry Spain in the afforestations made under the Afforestation of Agricultural Land European Program, since 1993. We study a 1998/1999 afforestation of a farm in Toledo, in two pieces of 50 ha. each, until that moment dedicated to dry farming grain crops. The slopeswere between 0 and 10%, with sandy soils. All the farm presents high density of small game species. The results obtained, with less than 8% faults after two years, under conditions of little rain in 1998/99, and very dry summer in 2000, answer for the afforestation method employed, and permit us recomend it for other farms.
Keywords: Agricultural land; dry regions; Holm oak; Kermes Oak